Copyright Protection for Songs Uploaded to the Spotify Digital Music Application Without Permission - Lesnussa, Maichel; Narwadan, Theresia Nolda Agnes; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Copyright holders can and have the right to determine who can use their work or not.However,Uploading songs by Spotify application users can unknowingly trigger copyright infringement.Purposes of the Research: To examine the legal relationship between the Spotify application and copyright holders and the form of copyright protection for songs uploaded on the Spotify application without permission.Methods of the Research: The research method used in this writing is the normative legal research method with a legislative approach, case approach and conceptual approach.Results of the Research: The legal relationship between the Spotify Music application and the Copyright Holder is based on a license agreement made in the form of an authentic deed and the form of legal protection of the creator's rights against uploading songs on the Spotify Music application without permission can be protected preventively and repressively. However, the most effective form of legal protection to be applied to this problem is the form of repressive legal protection.